Gastroenteritis and Transmission of Helicobacter pylori Infection in Households - Sharon Perry; Maria de la Luz Sanchez; Shufang Yang; Thomas D. Haggerty; Philip Hurst; Guillermo Perez-Perez; Julie Parsonnet (Emerging Infectious Diseases, 2006)
The mode of transmission of Helicobacter pylori infection is poorly characterized. In northern California, 2,752 household members were tested for H. pylori infection in serum or stool at a baseline visit and 3 months later. Among 1,752 person considered uninfected at baseline, 30 new infections (7 definite, 7 probable, and 16 possible) occurred, for an annual incidence of 7% overall and 21% in children <2 years of age. Exposure to an infected household member with gastroenteritis was associated with a 4.8-fold (95% confidence interval [CI] 1.4–17.1) increased risk for definite or probable new infection, with vomiting a greater risk factor (adjusted odds ratio [AOR] 6.3, CI 1.6–24.5) than diarrhea only (AOR 3.0, p = 0.65). Of probable or definite new infections, 75% were attributable to exposure to an infected person with gastroenteritis. Exposure to an H. pylori–infected person with gastroenteritis, particularly vomiting, markedly increased risk for new infection.